Synthesis of nanocrystalline rutile - Samuel, V; Pasricha, R; Ravi, V (Ceramics International, 2005)
Nanocrystalline titanium dioxide (TiO2) in the rutile phase has been obtained by homogeneous precipitation using urea and TiOCl2. A mixture of urea and TiOCl2 is heated on a hot water bath at 65-75 degrees C to precipitate rutile powders. X-ray diffraction (XRD) studies on these oven-dried powders indicated the formation of single-phase rutile. Raman scattering experiments were also performed to confirm the formation of the rutile phase. Transmission electron microscopy (TEM) investigations revealed the average particle size of these powders to be 40 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical preparation; Electron microscopy; powders; TiO2; X-ray methods